Self-Nanoemulsifying Drug Delivery System Loaded with Psiadia punctulata Major Metabolites for Hypertensive Emergencies: Effect on Hemodynamics and Cardiac Conductance - Abdallah, Hossam M.; El-Bassossy, Hany M.; El-Halawany, Ali M.; Ahmed, Tarek A.; Mohamed, Gamal A.; Malebari, Azizah M.; Hassan, Noura A. (Frontiers in Pharmacology, 2021)
Vasodilators are important class of antihypertensive agents. However, they have a limited clinical use due to the reflex tachycardia associated with their use which masks most of its antihypertensive effect and raises cardiac risk. Chemical investigation of Psiadia punctulata (PP) afforded five major methoxylated flavonoids (1-5) three of which (1,4, and 5) showed vasodilator activity. Linoleic acid based self-nanoemulsifying drug delivery system (SNEDDS) was utilized to develop intravenous (IV) formulations that contain compounds 1, 4 or 5. The antihypertensive effect of the prepared SNEDDS formulations, loaded with each of the vasodilator compounds, were tested in angiotensin-induced rat model of hypertension. Rats were subjected to real-time recording of blood hemodynamics and surface Electrocardiogram (ECG) while the pharmaceutical formulations were individually slowly injected in cumulative doses. Among the tested formulations, only that contains umuhenergin (1) and 5,3`-dihydroxy- 6,7,4`,5`-tetramethoxyflavone (5) showed potent antihypertensive effects. Low IV doses, from the prepared SNEDDS, containing either compound 1 or 5 showed a marked reduction in the elevated systolic blood pressure by 10 mmHg at 12 μg/kg and by more than 20 mmHg at 36 μg/kg. The developed SNEDDS formulation containing either compound 1 or 5 significantly reduced the elevated diastolic, pulse pressure, dicrotic notch pressure and the systolic- dicrotic notch pressure difference. Moreover, both formulations decreased the ejection duration and increased the non-ejection duration while they did not affect the time to peak. Both formulations did not affect the AV conduction as appear from the lack of effect on P duration and PR intervals. Similarly, they did not affect the ventricular repolarization as no effect on QTc or JT interval. Both formulations decreased the R wave amplitude but increased the T wave amplitude. In conclusion, the careful selection of linoleic acid for development of SNEDDS formulation rescues the vasodilating effect of P. punctulata compounds from being masked by the reflex tachycardia that commonly associated with the decrease in peripheral resistance by most vasodilators. The prepared SNEDDS formulation could be suggested as an effective medication in treatment of hypertensive emergencies, after clinical evaluation.